E-Transform: Development Of An Electronic Educational Quiz Board For Learning High-School's Mathematical Transformation - Azahar, Arman Hadi; Nor Shah, Mohd Badril; Zainal Abidin, Amar Faiz; Harun, Mohamad Haniff; Leong, Tian Yung; Mohd Yusof, Zakiah; Hasim, Saipol Hadi; Semail, Saifuddin (Seventh Sense Research Group, 2021)
Mathematical Transformation is a part of Mathematics Secondary grade syllabus in Malaysia where the students being exposed to three topics: translation, reflection and rotation. This paper is an extension of a published proceeding which proposed an educational kit that can be used to study the Topic of Transformation in Mathematics. The educational kit displays a question at an LCD screen in which student need to insert the correct shape at the appropriate slot at the given grid. Then, the educational kit gives feedback to the student. A survey is done to gauge the effectiveness of the educational kit. The result shows that the respondents agreed that the educational kit is suitable for the syllabus and catches the student’s attention. From the same feedback, there is a need to improve the instructional of the educational kit as there are a few respondents among the students do not feel the educational quiz board can be handle without supervision